Artificial intelligence, blockchain technology, and risk-taking behavior in the 4.0IR metaverse era: Evidence from Bangladesh-based SMEs - Mohammad Rashed Hasan Polas; Asghar Afshar Jahanshahi; Ahmed Imran Kabir; Abu Saleh Md. Sohel-Uz-Zaman; Abu Rashed Osman; Ridoan Karim (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
This study investigates the variables affecting the adoption of blockchain technology (BT) among small and medium-sized enterprises (SMEs) with the application of artificial intelligence (AI) via the mediating lens of risk-taking behavior. As an initial sample, 150 owners/top managers from 150 SMEs (one informant from each) in Dhaka, Bangladesh, were chosen. A stratified random sample was employed for this cross-sectional study. Applying structural equation modeling, the combined influence of internal and external variables influencing the intention to adopt BT is explored. Results show that: (1) knowledge of artificial intelligence has a positive and significant effect on the adoption of blockchain technology; (2) the relevant advantage of artificial intelligence has a positive and significant effect on the adoption of blockchain technology; (3) perceived ease of use of artificial intelligence has a positive and significant effect on the adoption of blockchain technology; (4) risk-taking behavior mediates the relationship between knowledge of artificial intelligence and adoption of blockchain technology; (5) risk-taking behavior does not mediate the relationship between relevant advantage and perceived ease of use of artificial intelligence with the adoption of blockchain technology. The current study is one of the few empirical investigations relating to SMEs using artificial intelligence and blockchain technologies for business operations. The study's limitations are the small sample size and use of a single informant. However, the findings on the adoption of blockchain technology have applications for boosting the competitiveness of SMEs. This study's originality stems from two factors: the novelty of blockchain technology and its potential to upend SMEs' conventional mode of operation. It highlights the need to consider the key variables affecting SMEs' adoption of blockchain technology with artificial intelligence.
Keywords: 650; artificial intelligence; Bangladesh; blockchain technology; risk-taking behavior; SMEs; survey